Development of an Interdisciplinary Literacy Instrument Integrating Mathematics, Science, and Arts Using a Construct-Centered Design Approach and Partial Credit Model: Analysis for Senior High School - Alimuddin; Irmayanti Irmayanti; Ahmad Alwi; Khadijah (Universitas Islam Ahmad Dahlan (UIAD), 2026)
The increasing emphasis on interdisciplinary literacy in STEAM-oriented education highlights the need for assessment instruments that can measure students’ ability to integrate mathematical, scientific, and artistic reasoning. This study aimed to develop and evaluate the quality of an interdisciplinary literacy assessment instrument for senior high school students using a Construct-Centered Design (CCD) framework and Item Response Theory (IRT) analysis. A quantitative pilot-study design was employed focusing on instrument development and psychometric evaluation. The participants were 10 Grade 10 senior high school students in South Sulawesi selected through purposive sampling who had completed instruction on systems of linear equations in two variables and trigonometry. The instrument consisted of five open-ended interdisciplinary tasks scored using a 0–4 polytomous rubric. Content validity was examined through expert judgment and quantified using Aiken’s V coefficient, while item characteristics were analyzed using the Generalized Partial Credit Model (GPCM) implemented in the R mirt package. The analysis included tests of unidimensionality, item parameter estimation, category functioning, reliability, and test information. The results showed that the instrument demonstrated very high content validity (average Aiken’s V = .93), measured a single dominant latent trait, and exhibited orderly functioning of the scoring categories. The empirical reliability coefficient was .926, indicating high measurement consistency. These findings suggest that the instrument is suitable for limited-scale implementation and has potential to support interdisciplinary literacy assessment within STEAM-oriented learning at the senior high school level.